Internet web pages – the way to support and educate cancer patients and their relatives, the American Cancer Society homepage as an example - Mackiewicz, Małgorzata; Grabarczyk, Piotr; Wysocki, Piotr (Contemporary Oncology/Współczesna Onkologia, 2000)
Continuing a cycle of articles devoted to oncology on internet, this time we have focused on education of oncological patients and their relatives. More and more such www services are being created. The American Cancer Society homepage contains twelve main links, which lead to such themes as: statistical analyses of cancer occurrence in American society, alternative methods of treatment, support for parents whose children have cancer, etc. Created for cancer patients and their relatives the www.cancer.org should become an example for analogical pages being constructed in polish internet.